Effects of Topical Application of Eupatorllum Odoratum, Channa Striatus, Centella Aslat Ica and Silver Sulphadiazine on Burn Wounds in an Animal Model - Mustafa, Nur Faizah (2005)
The merit of attempting to treat burn wounds has long been appreciated since the last century, at least in the sense of providing a clean wound, avoiding formation of purulent and exudation as well as to enhance a granulation and reepithelization. It has been a special consideration in medical practice as bum denatures cellular protein, inhibits cellular metabolism hence secondary interference of local vascular supply. Therefore, the present study was designed to investigate the effect of a crude methanolic extract of Eupatoriurn odoraturn, Channa striatus and Centella asiatica on burn wound healing as these natural resources have been traditionally used in burn treatment. A standard reproducible of second degree burn wounds was inflicted using a cylindrical stainless steel template (2.5 an diameter) on 225 adult male Sprague Dawley weighing between 250 - 350g. The animals were divided into five groups with nine animals in each group, representing a control and experimental groups. Extracts of Eupatoriurn odoraturn, Channa striatus and Centella asiatica with silver sulphadiazine, as a standard treatment were applied twice daily, except in the control group where wounds were left without any topical treatment. The rats were closely monitored to assess any changes. The rats were euthanized at 3, 7, 14, 21 and 28 days post burned. The macroscopic appearance of burn wounds was evaluated and recorded. The percentage of wound contractions was measured. The burn sites were excised and subjected to water content assessment and biomechanical study. Apart from that, histological study was also performed qualitatively and quantitatively using a hematoxylin and eosin and Masson's trichrome staining. Results obtained from this study revealed that from macroscopic study, Eupatoriurn odoraturn showed advanced effect to minimize the progression of zone of stasis as compared to other groups. Quantitative evaluation of the number of inflammatory cells (polymorphonuclear leucocytes, and macrophages) from day 3 to day 28 in wounds treated with Eupatoriurn odorafurn demonstrated sigruficant fall in number of inflammatory cells (polymorphonuclear leucocytes, and macrophages) from day 3 to day 28, whereas the number of proliferative cells (fibroblasts and endothelial cells) increased from day 7 to day 28. The Eupatorium odoratum also showed potential to preserve viable dermal tissue and induce a well-formed of angiogenesis with better organization as compared to other treatments. A semi quantitative wound scoring system used to evaluate the collagen bundles indicated that the Eupatorium odoratum treated burns demonstrated a better orientation of collagen as compared to other experimental groups as characterized by more densely packed fibres with thick bundles of wellaligned collagen and showed a basket-weave-like pattern with a more random structure. Eupatorium odoratum also promoted remodeling of collagen by synthesis of inter and intra-molecular protein crosslinking and thus produced a marked increased @<0.05) in tensile strength as compared to other experimental groups. Eupatorium odoratum also consistently prevented burn edema as shown by reduction in wet to dry weight ratio of - - the burn site tissues. On the other hand, burn wounds treated with Channa striatus showed earlier re-epithelialization as early as 3 days post burned while Eupatotium odoratum treated burn wounds at day 7. The results also demonstrated that burn wounds treated with Channa striahrs showed rapid cleansing of the wound with minimal scarring at day 28.In conclusion, the present study showed that the Eupatoriurn odoraturn was the most superior treatment agent for burn wounds followed by Channa striahcs and then Centella asiatica in relation to macroscopic evaluation, histological findings, edema measurement and biomechanical property.